Effects of Various Mung Bean Decoction Doses on Hematological Profile in Anemic Wistar Rats - Nabila Dwi Ayu Pratiwi; Hartalina Mufidah; Ahdiah Imroatul Muflihah (LPPM Universitas dr. Soebandi, 2025)
Background: Anemia remains a significant global public health problem, with iron deficiency being the primary cause. Mung beans (Vigna radiata L.) are nutritionally rich plants containing iron and glycine, which are essential for hemoglobin synthesis and red blood cell formation Purpose: This study aimed to evaluate the effects of various doses of mung bean decoction on hematological profile improvement in anemic Wistar rats induced with sodium nitrite (NaNO₂). Methods: An experimental study was conducted from June to August 2024 involving 25 male Wistar rats divided into five groups: healthy control (aquadest), negative control (NaNO₂), and three treatment groups receiving NaNO₂ followed by mung bean decoction at doses of 0.2 ml, 0.4 ml, and 0.8 ml respectively. Blood samples were collected before and after treatment for hemoglobin level assessment. Data were analyzed using paired sample t-test and One-way ANOVA with post-hoc Tukey tests. Results: The One-way ANOVA test showed highly significant differences in hemoglobin level changes between groups (p < 0.0001). The 0.2 ml dose group exhibited the highest hemoglobin increase from 8.12 g/dl to 17.70 g/dl (p = 0.0002), followed by the 0.4 ml dose group with an increase from 7.32 g/dl to 16.08 g/dl (p < 0.0001), and the 0.8 ml dose group with an increase from 6.40 g/dl to 14.16 g/dl (p = 0.0005). Conclusions: Mung bean decoction effectively improved hemoglobin levels in anemic Wistar rats, with the 0.2 ml dose demonstrating the most pronounced therapeutic effect.